PENGOLAHAN IKAN DI DAERAH ALIRAN SUMBER AIR PANAS BUMI DI DESA PAYO KABUPATEN HALMAHERA BARAT PROVINSI MALUKU UTARA - Abdurrachman Baksir; Nebuchadnezzar Akbar; M. Yunus Hi Abbas; Iswandi Wahab (JURNAL PERIKANAN TROPIS, 2020)
Potential geothermal water is located on the coast of West Halmahera Regency. The geothermal potential is utilized by the community as a medium of traditional medicine and local tourism. Utilization of hot water sources as a fish processing media has not been done. The purpose of this study was to determine fish processing using a modified oven in geothermal water flow. The research material is anchovy (Stolephorus indicus) measuring 10 cm. Fish drying equipment is made closed (airtight) as a whole. The process of fish maturation is done by laying the fish on the base located in the oven. The results showed that the fish cooked at room temperature 2 hours at room temperature 21 oC with geothermal water flow temperature 49oC-51 oC.